ARTIFICIAL INTELLIGENCE IN ANALYZING THE CAPITAL STRUCTURE EFFECT ON FINANCIAL STABILITY - Savina S. (Scientific Journal of Pedagogy and Economics, 2020)
Financial stability is an important measure used by stakeholders to assess the financial situation of an entity concerned. Economic worries caused by internal business issues, global processes, and international economic (regional) integration may increase the entity’s exposure to external factors. Financial stability considers the entity’s dependence on creditors and investors, i.e. the debt-to-equity ratio. Significant liabilities that are not fully covered by the entity’s own liquid funds create preconditions for bankruptcy should any large creditor demand settlement of any debts owed to it. However, borrowed funds can significantly increase the return on equity. Therefore, in analyzing financial stability, it is very important to use a system of indicators that indicate the entity’s future risks and profitability. Financial stability is the principal objective of financial analysis. The nature and scope of such economic analysis are aimed to determine the entity’s internal capacities, means, and methods for improving the entity’s financial stability. Thus, financial stability is understood as the entity’s guaranteed solvency and creditworthiness resulting from the effective formation, distribution, and application of financial resources in the entity’s business operations. Financial stability is assessed based on the working capital to inventory ratio and debt to equity ratio. Business entities are independent in establishing business relationships with their contract partners; therefore, they are fully responsible for the decisions they make. The increasing importance of financial analysis for the entity’s own financial situation and for its business partners is explained by the increasing demand for additional sources of business financing and the requirement to increase the productiveness of capital resources. Entity’s financial stability analysis should not focus on the current financial activities only. It should also determine what measures should be taken on a continuous basis to maintain and improve the entity’s financial situation. Both current and future stability, i.e. the entity’s sustainability, must be ensured to provide conditions for state-of-theart competitive production. An entity is a complex system consisting of many subsystems; therefore, a complex method must be applied to analyze its stability, i.e. using a system of financial stability indicators. Present-day diversity of financial stability indicators, including both absolute and relative indicators, makes the analysis difficult and overcomplicated, creating difficulties in combining the findings of the analysis to make conclusions about the entity’s financial stability. Absolute indicators, namely equity, borrowed capital, assets, cash, accounts receivable and accounts payable, profit, play an important role in the analysis of an entity’s financial stability. Equally important are absolute indicators calculated in the analysis of financial statements: net assets, working capital, working capital to inventory ratio, stable liabilities. These indicators are criterial as they are used to establish the criteria used in the financial analysis. An entity should have a flexible structure of financial resources and, if necessary, be able to borrow funds. Therefore, another manifestation of an entity’s potential financial stability is its creditworthiness, i.e., the ability to settle its payment obligations when due. Thus, an entity is considered creditworthy if it meets a certain requirement for granting a loan and is able to repay the loan when due subject to any interest accrued. This concept is closely related to the concept of financial stability and shows whether the company is able to raise funds from different sources to repay its debts. Credit analysis may predict solvency and is closely related to the analysis of solvency, financial stability and return on equity. Entity’s stable operation, high profitability and working capital turnover also guarantee loan repayment to a certain degree.